Improved Analysis Animals and Plants in My House (IPA) through The Discovery Learning Method Class IV - Wahyu Hidayat (Social, Humanities, and Educational Studies (SHEs): Conference Series, 2020)
In improving the achievement of students in science lessons, especially in the discussion of animals and plants in my home environment, the fourth grade students at SD Negeri Tombo 02 were selected using the discovery learning method. Discovery learning method is a teaching method that focuses on the activities of students in learning. In the learning process with this method, the teacher only acts as a guide and facilitator who directs students to find concepts, arguments, procedures, algorithms and the like. Thus students are encouraged to be more actively involved in learning materials and develop critical thinking skills in fourth grade students of SD Negeri Tombo 02, Bandar District, Batang Regency, 2020/2021 school year. After analyzing the value of the science learning process and results, the authors summarize the problems that occur in online learning, including: a. Students are less able to mention animals and plants, b. Students are less able to explain the parts of plant functions for humans, c. Students' perspectives are less able to explain the Indonesian landscape. From the results of the problem analysis above, it can be analyzed, including: Is the problem caused by inappropriate media or learning devices, learning materials that are not in accordance with the interests of students, or learning methods do not attract students.